Psychological adjustment of immigrants - Kocjančič, Cvetka (Two Homelands, 2000)
The psychological problems of immigrants and their adjustment to a new land were the subject of many contemporary studies in the field of psychology, sociology and anthropology.Their findings systematically confirm more frequent incidences of mental illness among immigrants. However, there are so many variables affecting migration that no specific conclusion could be drawn as to the causes of this phenomenon. The motivation for migration has to be taken into account, as well as migrants’ personalities, the extent of their losses and their personal coping strategies, other traumatic events related to their migration, the attitude of the host country and its immigration policies, etc. Three different waves of Slovene immigrants to Canada experienced different degrees of culture shock and they devised different coping strategies. All three seem to utilize the power of religion, as well as the community support of various Slovene organizations, to cope with the anxiety caused by the unknown and unexpected.